Persistent mercury hot spot in Central Europe and Skalka Dam reservoir as a long-term mercury trap - Hošek, M; Bednárek, J; Popelka, J; Elznicová, J; Tůmová, Š; Rohovec, J; Navrátil, T; Matys Grygar, T (Environmental geochemistry and health, 2020)
This study aimed to evaluate the relevance of the floodplain pollution sinks of the legacy mercury (Hg) hot spot in Kössein-Röslau river system (east Bavaria, Germany) for further mobilisation and fluvial transport of mercury in suspended particulate matter (SPM), as an important transport medium of Hg in aquatic systems. The channel belt fluvial erosion as the secondary pollution pathway was also considered. The hot spot has originated from the production of Hg compounds such as C2H5HgCN and C6H5HgCl in Chemical Factory Marktredwitz, and even more than 30 years after the factory abandonment, the Kössein and the Röslau rivers still export polluted fine grained SPM (median 25-35 μm) with mean annual concentrations of 17.4 mg/kg. SPM sampling was performed by floating samplers, supported by floodplain drill cores and by recent channel sediments manually collected along the polluted rivers further. Based on long-term monitoring data set from state enterprise Povodí Ohře, fish in the Skalka Reservoir have had Hg concentrations in their muscles up to 6 mg/kg for at least the last 14 years, exceeding the European maximal limit of 0.5 mg/Hg/kg. In addition, the Hg inventory in the Kössein-Röslau river stretches was therefore calculated; it produced an estimate of ca. 21 t Hg in a 22-km-long channel belt, prone to fluvial remobilisation during floods. Although a major portion of the fluvially transported Hg has yet been trapped by the Skalka Reservoir, the Hg content in the SPM exported farther downstream still varies between 2 and 10 mg/kg Hg. Due to the considerable Hg inventory in the Kössein-Röslau rivers, an improvement will not occur downstream unless specific measures target the secondary pollution mechanism(s).
Keywords: monitorování životního prostředí; pevné částice; Mercury compounds; Environmental Monitoring; Geologic Sediments; Legacy pollution; Německo; rtuť; řeky; Rivers; chemické látky znečišťující vodu; geologické sedimenty; Mercury; Water Pollutants, Chemical; záplavy; zvířata; Sediment reworking; Germany; Ohře floodplain; Particulate Matter; Floods; Fishes; Eger river; ryby; Fluvial system; Animals